Hypothetical Art and Art Education: The Educational Role of the Method of Hypothetical Artwork Modelling - Jurij Selan (University of Ljubljana, 2011)
A hypothetical artwork is an artwork that exists only as a fictional creation of an art theorist. The explicatory powers of such hypothetical artworks are mainly used by an art theorist to reflect on an art theoretical issue under consideration. Such an artwork has an intriguing and paradoxical nature. On the one hand, it is only fictitious, but, on the other hand, it tries to function as a real token, persuading the reader to trust it as if it were a real artwork. Even though this kind of argumentation can be deceiving, as it presents a statement of real art on the basis of fiction, it has some important explicatory abilities that can be put to good use in the art educational process. In this case, the construction of the hypothetical artwork is handled as the construction of a theoretical model. The author calls such theoretical construction the method of hypothetical artwork modelling, and its result the hypothetical artwork model. Such a hypothetical artwork model can be usefully employed when one wishes to encourage the student to become fictionally involved in the process of creation of an artwork, thus giving him or her more personal experience of problems that accompany the process of creating a real artwork. When such hypothetical experience is gained, the student can more efficiently learn about the considered art issue. In the paper, the author demonstrates how the explicatory powers of the method of hypothetical artwork modelling can be put into educational practice regarding an issue taken from colour theory (i.e., the primary colours fallacy).